2017
DOI: 10.1016/j.jacc.2016.10.062
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes Among Older Patients Receiving Implantable Cardioverter-Defibrillators for Secondary Prevention

Abstract: Almost 1 in 5 older patients receiving a secondary prevention ICD survives at least 2 years. High hospitalization and SNF admission rates, particularly among the oldest patients, identify substantial care needs after device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…A noteworthy example of this scenario is the need for hospitalization and admission to skilled nursing facilities in 4 of every 5 elderly patients who received an implantable cardioverter-defibrillator for secondary prevention of sudden cardiac death, even though they survived at least 2 years. 30…”
Section: General Aspects Of Old Age Risk Factors and Preventionmentioning
confidence: 99%
“…A noteworthy example of this scenario is the need for hospitalization and admission to skilled nursing facilities in 4 of every 5 elderly patients who received an implantable cardioverter-defibrillator for secondary prevention of sudden cardiac death, even though they survived at least 2 years. 30…”
Section: General Aspects Of Old Age Risk Factors and Preventionmentioning
confidence: 99%
“…Octogenarians had a LOS of 3.0 ± 3.4 days (versus younger cohort = 2.8 ± 3.2 days) and were at a three‐time higher risk of being discharged to SNF rather than home (12.5% versus 4.8% in younger cohort), which has been repeatedly validated for other cardiovascular and trauma hospitalizations . The interpretation of LOS should be taken with caution because although, the values are statistically significant, the clinical implication of discharging a patient after 2.8 days versus 3.0 days is not practical.…”
Section: Discussionmentioning
confidence: 99%
“…While outcomes of the 2 groups could not be formally compared in the present study due to small sample sizes, numerically, the rates of death in the ICD registry were comparable to those observed in ICD recipients in the AVID trial. Also, a recent analysis of the NCDR ICD Registry showed that almost 4 in 5 older patients receiving a secondary prevention ICD survive at least for 2 years [14]. A trial of secondary prevention ICDs versus no ICDs in a contemporary cohort will likely never be feasible due to the widespread acceptance of the importance of the ICD in such high-risk populations.…”
Section: Discussionmentioning
confidence: 99%